Parámetros de calidad espermática en semen crioconservado de peces dulceacuícolas (Orinoquia, 2022)
Aquaculture worldwide is becoming more and more relevant and has become a source of food and economic income for many communities around the world. However, activities such as the overexploitation of water and fishing resources, the increase in the human population, environmental pollution, climate change, among other factors, are putting at risk not only the food security of the planet, but also the biodiversity of organisms, including fish. One of the tools to safeguard aquatic biological resources is cryopreservation, which in fish focuses mainly on the conservation of semen in liquid nitrogen and this, despite being a very useful technique, is susceptible to improvement, since it has been reported that the low temperatures used in cryopreservation can cause negative effects on sperm cells, due to this it is necessary to establish specific species protocols to get the full potential of this form of conservation. Therefore, the objective of this review is to gather information on the main sperm quality parameters that are affected at the time of cryopreservation of semen, with emphasis on freshwater species.
Keywords: aquaculture, sperm quality, semen